The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/8360841
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Characterization of a Missense Variant of MLH1 Identified in Lynch Syndrome Pedigree

Abstract: Lynch syndrome (LS) is the most common hereditary colorectal cancer (CRCs) inherited in an autosomal-dominant manner. Here, we reported a multigeneration Chinese family clinically diagnosed with LS according to the Amsterdam II criteria. To identify the underlying causative gene for LS in this family, whole-exome sequencing (WES) was performed. A germline missense variant (c.2054C>T:p.S685F) in exon 18 of MLH1 was successfully identified by WES. Sanger sequencing verified the results of WES and also confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Currently, cheap accessible immunohistochemistry (IHC) technology has been widely used in China to detect MMR protein expressions [ 29 ]. MLH1 missense variant caused the defects in MLH1 and PMS2 proteins expressions [ 19 ], and MSH6 mutation and rarely MSH2 mutation resulted in loss of MSH6 protein expression [ 23 ]. Studies had shown that the sensitivity and specificity of IHC to detect MMR protein mutations were 66.7-90 % and 89-97.3 %, respectively [ 13 , 18 , 23 ].…”
Section: Screening and Diagnosing Criteria And Methodsmentioning
confidence: 99%
“…Currently, cheap accessible immunohistochemistry (IHC) technology has been widely used in China to detect MMR protein expressions [29]. MLH1 missense variant caused the defects in MLH1 and PMS2 proteins expressions [19], and MSH6 mutation and rarely MSH2 mutation resulted in loss of MSH6 protein expression [23].…”
Section: Screening and Diagnosing Criteria And Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies have also described the absence of protein expression due to the presence of missense gene variants. [36,37] The mechanism accounting for enhanced mRNA degradation in these cases is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%